"Vi ler ikke av deg, vi ler med deg!": Racehumor og skam i norske flygtningefilm - Oxfeldt, Elisabeth (K&K - Kultur og Klasse, 2018)
The article analyzes Jan Vardøen’s House of Norway (2016) and Rune Denstad Langlo’s Welcome to Norway! (2016) as multicultural and multiracial film comedies that set out to ridicule and shame Norwegians at the height of the Syrian refugee crisis. My focus is on their portrayal of various forms of Norwegian racism. I start out by situating the films within a Norwegian social and political landscape. I then outline my theoretical and methodological point of departure (Bergson, Berlant and Ngai) and turn to relevant comedy subgenres. In my analysis of House of Norway, I discuss the shaming of Norwegians who, in their encounter with refugees, tend to be overly nationalistic, insisting on a Norwegian identity rooted in 19th-century national romanticism. In the case of Welcome to Norway!, the shameless Norwegian is simply cold and cynical. Ultimately, my point is that the films expose many relevant forms of Norwegian racism without being entirely racially innocent themselves. As comedies dealing with the topic of racism, they cannot be expected to be entirely innocent either, in part because laughter and shame are not just one thing, serving one function. Audiences may laugh for various reasons, feel shame for various reasons, and use that shame to strengthen a community – in ways that variously include and exclude the other. The comedies are nevertheless significant cultural objects, exposing Norwegian racisms as they come to the fore in the current encounter with refugees.